Relation between attempted suicide and suicide rates among young people in Europe. Issue 3 (March 1998) - Hawton, K; Arensman, E; Wasserman, D; Hultén, A; Bille-Brahe, U; Bjerke, T; Crepet, P; Deisenhammer, E; Kerkhof, A; De Leo, D; Michel, K; Ostamo, A; et al.
Abstract : STUDY OBJECTIVE: To determine if there are associations between rates of suicide and attempted suicide in 15-24 year olds in different countries in Europe. DESIGN: Attempted suicide rates were based on data collected in centres in Europe between 1989 and 1992 as part of the WHO/EURO Multicentre Study of Parasuicide. Comparison was made with both national suicide rates and local suicide rates for the areas in which the attempted suicide monitoring centres are based. SETTING: 15 centres in 13 European countries. PATIENTS: Young people aged 15-24 years who had taken overdoses or deliberately injured themselves and been identified in health care facilities. MAIN RESULTS: There were positive correlations (Spearman rank order) between rates of attempted suicide and suicide rates in both sexes. The correlations only reached statistical significance for male subjects: regional suicide rates, r = 0.65, p < 0.02; national suicide rates, r = 0.55, p < 0.02. CONCLUSIONS: Rates of attempted suicide and suicide in the young covary. The recent increase in attempted suicide rates in young male subjects in several European countries could herald a further increase in suicide rates.